Stoichiometric homeostasis of Morus alba in the dry-hot valley - Guo, Haixia; Luo, Sheng; Chen, Siyuan; Li, Yike; Zhang, Jianhua; Chen, Guantao; Wang, Xie (Frontiers in Plant Science, 2025)
IntroductionStoichiometric homeostasis is an important strategy used by plants to function optimally in changing environments.MethodsIn order to investigate whether plants under stricter resource restrictions exhibit stronger homeostasis, this study took M. alba inhabiting in a dry-hot valley as the research subject.ResultsThe stoichiometry of M. alba leaves, their variations in response to altitude and slope, and their correlations with soil were analyzed. The results showed that soil nutrient levels were higher on the shady slope compared to the sunny slope, and responded differently to altitude on the two slopes. On the sunny slope, soil carbon (C) content increased significantly with altitude, whereas on the shady slope, soil phosphorus (P) content decreased with increasing altitude. The C: N and C: P ratios of the soil were lower than the average in China. The C: N and C: P ratios of M. alba leaves were lower than those of global and Chinese forest ecosystems. The N: P ratio of M. alba leaves was < 14. However, no significant correlation was observed between M. alba leaves and soil C, N, P, or stoichiometric characteristics. The changes in C, N, and P and their ratios in M. alba leaves did not correspond with those in the soil. M. alba exhibited "strict homeostasis" on both sunny and shady slopes.DiscussionThe results suggest that M. alba's growth is limited by nutrients availability, particularly nitrogen. The strict stoichiometric homeostasis is an adaptation strategy for M. alba in dry-hot valleys to alleviate nutrient limitations, which leads to a decoupling of ecological stoichiometry between M. alba leaves and soil.